RANCANGAN UNDANG UNDANG PEMBERANTASAN TINDAK PIDANA KORUPSI (SEBUAH TANGGAPAN) - Sudhono Iswahyudi (Faculty of Law, Universitas Diponegoro, 2013)
Abstract This article presents the comments about the draft of the reform of the Act number 31 year 1999 as being changed by Act number 20 year 2001 about The Eradication of Corruption. Since 2006 Indonesia had ratificated The United Nations Convention Against Corruption (UNCAC) 2003 by the Act number 7 year 2006. The purpose of this article is how to harmonized between the aims for eradication corruption by refered the UNCAC 2003, and the other side how to accommodations of social justice analysing, comprehend the development of national criminal law policy on the eradicating corruption in Indonesia, analysing national criminal law policy on the eradicating corruption in Indonesia after the United Nations Conventions Against Corruption (UNCAC) 2003 ratification. This comment also purposed how the UNCAC 2003 could be aplicated and be implemented in the regulations and statutes that become the fundamental law for law enforcement on eradicating corruption in Indonesia. Keyword : the eradication of corruption, comments. Abstrak Artikel ini menyajikan tanggapan tentang rancangan perubahan UU No. 31 Tahun 1999 sebagaimana yang diubah dengan UU No. 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi. Sejak tahun 2006 Indonesia telah meratifikasi Konvensi PBB Melawan Korupsi (UNCAC) 2003 ke dalam Undang-undang Nomor 7 tahun 2006. Tujuan artikel ini adalah bagaimana mengharmonisasi tujuan pemberantasan korupsi sebagaimana UNCAC 2003, dan sisi lain bagaimana mengakomodasi analisis keadilan sosial, juga memahami perkembangan kebijakan hukum pidana nasional pada pemberantasan korupsi di Indonesia, menganalisis kebijakan hukum pidana nasional pada pemberantasan korupsi di Indonesia setelah Konvensi PBB Melawan Korupsi (UNCAC) 2003 diratifikasi. Tanggapan ini juga bertujuan bagaimana UNCAC 2003 dapat diaplikasikan dan diimplementasikan dalam peraturan dan undang-undang yang menjadi dasar hukum untuk penegakan hukum terhadap pemberantasan korupsi di Indonesia. Kata Kunci : pemberantasan tindak pidana korupsi, tanggapan.